Efficacy and safety of heart rate control with esmolol on the incidence and duration of organ failure in predicted severe acute pancreatitis: protocol of a multicenter, open-label, randomized controlled trial - Mingfeng Huang; Rong Wei; Lu Ke; Weijian Li; Jian Song; Haibin Ni; Xiaofei Huang; Yun Sun; Lu Fu; Yanhua Li; Dong Zhang; Bin Han; et al. (Frontiers in Medicine, 2025)
IntroductionOveractivation of the sympathetic nerve system can lead to a sustained increase in heart rate, which may impair blood perfusion and organ function. Previous studies have demonstrated that the use of β-blockers like esmolol can reduce heart rate, thereby improving clinical outcomes in patients with septic shock. For acute pancreatitis (AP), which shares a similar inflammatory pathophysiology with sepsis, previous experimental and observational studies showed significant sympathetic excitation during the acute phase, and the use of β-blockers might be clinically beneficial. This study aims to test the hypothesis that early intravenous esmolol administration to control heart rate will improve the incidence and duration of organ failure in patients with predicted severe acute pancreatitis (pSAP).MethodsThis is an investigator-initiated, multicenter, open-label, randomized controlled trial. All patients with pSAP who still exhibit elevated heart rate (≥110 bpm) after 6 h of adequate intravenous fluid resuscitation within the first 72 h of symptom onset will be screened for eligibility. A total of 146 participants will be randomized to receive either esmolol or standard care. Patients in the esmolol group will receive a continuous esmolol infusion to maintain a heart rate between 80 and 94 beats per minute (bpm) within the first 96 h of randomization. The primary endpoint is organ failure free and alive days (OFFDs) to day 14 after trial entry. Secondary endpoints are comprised of both process and clinical measures, including heart rate variability, the proportion of patients’ heart rate recovered to <95 bpm, changes in plasma interleukin-6 and C-reactive protein between day 1 and day 5, in hospital and 90-day mortality, new-onset organ failure, free and alive days to day 30 for intensive care admission, and requirement of mechanical ventilation, vasopressor use, and renal replacement therapy.DiscussionThis study will provide top-class evidence concerning the effects of heart rate control with a classic β-blocker on the incidence and duration of organ failure in patients with pSAP and increased heart rate.Ethics and disseminationThis study has been approved by the ethics committee of Jinling Hospital, Nanjing University (2022DZKY-076-02) and all participating sites. Results will be disseminated through peer-reviewed journals and scientific conferences.Trial registrationIdentifier, ChiCTR2400080160.